Solvent-Induced Polymorphism of Iron(II) Spin Crossover Complexes - Šalitroš, Ivan (Materials (Basel), 2016)
Two new mononuclear iron(II) compounds (1) and (2) of the general formula [Fe(L)(2)](BF(4))(2)·nCH(3)CN (L = 4-(2-bromoethyn-1-yl)-2,6-bis(pyrazol-1-yl)pyridine, n = 1 for (1) and n = 2 for compound (2)), were synthesized. The room temperature crystallization afforded concomitant formation of two different solvent analogues: compound (1) exhibiting triclinic P-1 and compound (2) monoclinic C2/c symmetry. Single-crystal X-ray studies confirmed the presence of the LS (low-spin) state for both compounds at 180 K and of the HS (high-spin) state for compound (2) at 293 K, in full agreement with the magnetic investigations for both solvent polymorphs. Compound (1) exhibits spin transition above 293 K followed by subsequent solvent liberation, while the spin transition of (2) takes already place at 237 K. After complete solvent removal from the crystal lattice, compound (1d) (the desolvated polymorph derived from (1)) exhibits spin transition centered at 342 K accompanied by a thermal hysteresis loop, while the analogous compound (2d) (the desolvated derivate of compound (2)) remains blocked in the HS state over all the investigated temperature range.